Լոլիկի ողկուզավոր հիբրիդների պտուղների որակական ցուցանիշների ուսումնասիրումը և գնահատումը ջերմատան պայմաններում - Մարտիրոսյան, Հ. Հ. (ՀԱԱՀ հիմնադրամ)
Լոլիկի ողկուզավոր հիբրիդների պտուղների որակական ցուցանիշների ուսումնասիրության նպատակով ընտրվել են ներմուծված Rijk Zwaan ֆիրմայի Prodezo F1, Santiana F1, Adventure F1, Syngenta ֆիրմայի Climbo F1 և տեղական RM-4 (Սյունե) հիբրիդները: Ըստ սորտային առանձնահատկությունների և աճեցման շրջապտույտի՝ հետազոտվող հիբրիդներում չոր նյութերի պարունակությունը տատանվել է 6,14-7,74 %, շաքարներինը` 2,88-3,22 %, վիտամին C-ինը՝ 18,44-22,13 մգ% սահմաններում: Հետազոտությունների արդյունքների համաձայն՝ բարձրորակ պտուղներ ունեցող Rijk Zwaan ֆիրմայի Adventure F1 և տեղական RM-4 (Սյունե) հիբրիդներն առաջարկում ենք ներդնել Հայաստանի ջերմատնային տնտեսությունների պայմաններում ողկուզավոր լոլիկի արտադրությունում: Для изучения качественных показателей плодов гибридов кистевых томатов были отобраны импортные гибридные сорта Prodezo F1, Santiana F1, Adventure F1 компании Rijk Zwaan, Climbo F1 фирмы Syngenta и местный RM-4 (Сюне). В зависимости от сортовых особенностей и цикла выращивания содержание сухого вещества в исследуемых гибридах колебалось в пределах 6.14-7.74 %, сахаров – 2.88-3.22 %, витамина С – 18.44-22.13 мг%. С учетом полученных результатов предлагаем гибрид Adventure F1 компании Rijk Zwaan и местный RM-4 (Сюне) с высоким качеством плодов внедрить в производство кистевых томатов в условиях теплиц Армении. The increased demand for tomato products has spurred the cultivation of various varieties and hybrids. Particularly notable are the tomato hybrids whose fruits are harvested collectively in entire branches (racemes), thus earning them the name “raceme tomatoes”. The scientific studies were carried out in 2021-2023, in the glass experimental greenhouse of the Scientific Center of Vegetable and Industrial Crops of the Ministry of Agriculture of the RA, Darakert, Ararat Marz, during two vegetation periods: spring and autumn. The study focused on five raceme tomato hybrids: Prodezo F1, Santiana F1, Adventure F1 by Rijk Zwaan, Climbo F1 by Syngenta, and hybrid RM-4, which was obtained by us (Known since 2023 as Syune). Prodezo F1 hybrid, which is included in the state register of Armenia, served as the control. The selection of hybrids was based on the increasing demand among the population for raceme tomatoes. According to varietal characteristics and vegetation period, the dry matter content varied from 6.14 % to 7.74 %, which was 2.88 % - 3.22 % for sugars, and 18.44 % - 22.13 % for ascorbic acid content. As a result of the study, the hybrids Adventure F1 by Rijk Zwaan and RM-4 (Syune), a locally cultivated hybrid, stood out for their quality indicators among the examined tomato hybrids, regardless of the vegetation period. These high-quality hybrids will be introduced to greenhouses of Armenia for further cultivation.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա